PERJUANGAN ORGANISASI GURU DI MASA REVOLUSI SEJARAH PGRI DI AWAL PENDIRIANNYA - Ahmad Kosasih (Sosio e-Kons, 2016)
Early education in independent Indonesia become one of the important aspects to foster the spirit of nationalism and promoting the ideals of independence of the Republic of Indonesia. Indonesian government attention newborn and some of the figures revolutionist who realized that education is very important to foster the spirit of nationalism and efforts to create awareness of an independent nation. Based on the subjects of education and new teaching drafted by the Committee of Inquiry Teaching goals and educational foundation and a system of schooling that characterizes to Indonesiaan. Organization of Indonesian Teachers Association, as a teachers Indonesian container that has been since the days of the Dutch East Indies. Since the proclamation of PGRI organization establishes itself as a fighter who helped defend the independence and sovereignty of Indonesia NKRI. This organization is a manifestation of the Indonesian teacher in taking part and responsibility in accordance with his profession as an educator for the independence aspired. The organization therefore seen as a unifier of teachers who are: 1) a unitary, 2) independent, 3) non-political. It is also a tool, a vehicle in the interests of the teachers for their professional development, education in general and devotion to the homeland and the nation. Keywords: History of education; nationalism; Indonesian revolution; PGRI